Laryngeal and Tracheobronchial Infections of the Pediatric Airway - Ida, Jonathan B. (Journal of Pediatric Infectious Diseases, 2019)
Infections of the pediatric airway result in partial obstruction of the airway and often require intervention to maintain the airway. Most airway infections are treated medically, but respiratory support or invasive airway protection may be required if the patient does not respond adequately to initial interventions. We review three major types of central airway infections, focusing on illustrative diagnostic and treatment dilemmas.
Keywords: airway infections; croup; stridor; cough; tracheitis; protracted bacterial bronchitis